A crustal profile of the heat production of the Harts Range Group, Northern Territory. Issue 1 (1st December 2019) - Pollett, Alicia; Raimondo, Tom; Hand, Martin; Peters, Stefan
Summary: Medium pressure-high temperature (MP-HT) metamorphism is generally accepted to be driven by crustal thickening within compressional tectonic regimes. Despite this consensus, the Harts Range Group located in central Australia provides evidence for MP-HT metamorphism occurring as a result of burial in a deep intracontinental rift. Detrital zircon studies of metasediments within the Harts Range and surrounding sedimentary sequences indicate that the Harts Range Group represent the metamorphosed equivalents of the sedimentary successions located in the neighbouring Late Neoproterozoic to Cambrian Amadeus and Georgina Basins. Whilst the metamorphic character of this region has been studied, the thermal character of each of the individual sequences that infilled the rift are yet to be examined. The exhumation and preservation of all metamorphosed components of the Harts Range rift basin, along with the proximity of these metasediments to their protolith equivalents, provide a unique opportunity to examine the heat production of components that infilled the rift throughout the Cambrian. We undertake a field study to measure heat production across three lithological units that comprise the Harts Range Group. We also apply heat production calculations to calibrated airborne radiometric datasets in order to calculate the approximate heat production of these sedimentary sequences when buried to 30 km depth. We use the ground-sourced measurements as a tool to validate our derivation of heat production from airborne radiometrics. If statistically sound, we are then able to use the airborne radiometric dataset to calculate average heat production and relative heat flow of each succession contained within the rift. This can provide insights into the thermal drivers of medium pressure-high temperature metamorphism in an extensional intracratonic tectonic setting.